Gender Representation in Da’wah Programs on RRI Purwokerto - Uswatussolihah, Uus; Turhamun, Turhamun (Yinyang: Jurnal Studi Islam Gender dan Anak, 2024)
This article examines gender representation in the Islamic da’wah program on Radio Republik Indonesia (RRI) Purwokerto. The study employs a descriptive-qualitative method, using Norman Fairclough’s discourse analysis approach. Fairclough’s model consists of three levels of analysis: text analysis, discourse practice, and sociocultural practice. The text analysis in this study focuses on the event format and the materials from the guest speakers. Discourse practice analysis looks at how texts are produced and consumed, while sociocultural practice analysis addresses three aspects: situational, institutional, and social. The research findings reveal that gender representation in Islamic da’wah/religious programs on radio in Purwokerto still reflects gender inequality. This inequality can be observed through Fairclough’s three levels of discourse analysis. At the text level, some guest speakers continue to present a mindset that positions men in a superior role compared to women. RRI has not yet provided a space for the ongoing transformation of ideas about equality, such as issues related to early marriage, human trafficking, and so on. The themes discussed mainly focus on morals, jurisprudence, and worship. At the discourse practice level, the guest speakers and broadcasters involved are predominantly male. At the sociocultural practice level, the study shows that the gender representation in da’wah programs at RRI Purwokerto reflects an unequal gender construction in the broader society. This research recommends that radio managers provide more opportunities for female guest speakers and incorporate themes on gender justice.